2022
DOI: 10.3390/children9040536
|View full text |Cite
|
Sign up to set email alerts
|

Second and Third Generational Advances in Therapies of the Immune-Mediated Kidney Diseases in Children and Adolescents

Abstract: Therapy of immune-mediated kidney diseases has evolved during recent decades from the non-specific use of corticosteroids and antiproliferative agents (like cyclophosphamide or azathioprine), towards the use of more specific drugs with measurable pharmacokinetics, like calcineurin inhibitors (cyclosporine A and tacrolimus) and mycophenolate mofetil, to the treatment with biologic drugs targeting detailed specific receptors, like rituximab, eculizumab or abatacept. Moreover, the data coming from a molecular sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It has been observed that oral glucocorticoid therapy in children with nephrotic syndrome may encounter issues of resistance, with approximately 50% of affected children eventually progressing to end-stage kidney disease if unresponsive after five years of treatment ( 149 ). Consequently, the implementation of specific immunosuppressive therapies, including drugs such as cyclophosphamide, has become necessary ( 150 ). The combination of alkylating agents with steroids has demonstrated high efficacy in managing high-risk podocyte-associated proteinuric kidney diseases such as MN ( 151 ).…”
Section: Therapeutic Strategies Targeting Immunity In Podocyte Injurymentioning
confidence: 99%
“…It has been observed that oral glucocorticoid therapy in children with nephrotic syndrome may encounter issues of resistance, with approximately 50% of affected children eventually progressing to end-stage kidney disease if unresponsive after five years of treatment ( 149 ). Consequently, the implementation of specific immunosuppressive therapies, including drugs such as cyclophosphamide, has become necessary ( 150 ). The combination of alkylating agents with steroids has demonstrated high efficacy in managing high-risk podocyte-associated proteinuric kidney diseases such as MN ( 151 ).…”
Section: Therapeutic Strategies Targeting Immunity In Podocyte Injurymentioning
confidence: 99%